Role of Interionioc Interactions on the Surface Properties of Liquids Zn, Sn and Pb (Bangladesh Journal of Physics, 2023)
Surface tension ( ) formula based on hard-sphere (HS) interaction developed from first and second order Percus-Yevick (PY) solutions for isothermal compressibility proposed by Mayer et al. has been used to calculate surface tension of liquid less simple metals Zn, Sn, and Pb. For calculation of surface entropy ( ) of same metals, we have used the formula of Gosh et al. Effective HS diameter and corresponding packing fraction are key components of the employed HS theories. These components are calculated by utilizing Bretonnet-Silbert (BS) pseudopotential for interactions in metals and the Linearized Week-Chandler-Andersen (LWCA) theory for describing liquid structure. Potential profile has been changed two ways; firstly, by changing the local field correction functions proposed by Vashishta-Shingwi (VS) and Ichimaru-Utsumi (IU) and secondly, by changing the model parameter  (the  electron occupancy number). We observe that the variation of Zs and local field correction functions changes the potential profile, especially, the depth and position of the principal minimum. Position of the principal minimum is responsible for estimation of effective HS diameter. Surface properties of the concerned systems have been changed a little bit with different values of effective HS diameter. Calculated results of  suggest that first order approximation of PY solution for  works better than that of second order.Bangladesh Journal of Physics, Vol. 30, Issue 1, pp. 23–34, June 2023